Nigrosome-1 on Susceptibility Weighted Imaging to Differentiate Parkinson’s Disease From Atypical Parkinsonism: An In Vivo and Ex Vivo Pilot Study - Meijer, Frederick J.A. (Pol J Radiol, 2016)
BACKGROUND: Previous case-control studies have suggested that the absence of a swallow-tail appearance in the substantia nigra on high-resolution SWI, representing nigrosome-1, has high accuracy to identify Parkinson’s disease (PD). The first goal of our study was to evaluate nigrosome-1 ex vivo using optimized high-resolution susceptibility sensitive MRI. Our second goal was to evaluate its diagnostic value in vivo using a clinical 3T SWI sequence to differentiate between PD and atypical parkinsonism (AP) in a cohort of patients with early-stage parkinsonism. MATERIAL/METHODS: Case-control pilot study to evaluate nigrosome-1 ex vivo (2 PD, 2 controls), using high-resolution susceptibility sensitive sequences at 11.7 T MRI. Next, evaluation of nigrosome-1 in vivo using a clinical 3 T SWI sequence in a prospective cohort of 60 patients with early-stage parkinsonism (39 PD, 21 AP). Moreover, 12 control subjects were scanned. The bilateral substantia nigra was evaluated by two neuroradiologists for the presence, absence or indecisive presence of nigrosome-1. The discriminative power was evaluated by Receiver-Operating Characteristic. RESULTS: We identified nigrosome-1 in ex vivo control subjects. Nigrosome-1 was not identified in the ex vivo PD cases. In our prospective clinical cohort study, the AUC for the swallow-tail sign to discriminate between PD and AP was 0.56 (0.41–0.71) for reader 1 and 0.68 (0.55–0.82) for reader 2. CONCLUSIONS: The diagnostic accuracy of the swallow-tail sign was marginal to discriminate between PD and AP using our clinical 3 T SWI sequence.